2002
DOI: 10.1093/jn/132.4.665
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Zinc Deficiency Inhibits Chondrocyte Proliferation and Induces Cell Apoptosis in the Epiphyseal Growth Plate of Young Chickens

Abstract: The purpose of this study was to investigate the effect of zinc deficiency on chondrocyte proliferation, differentiation and apoptosis in the epiphyseal growth plate of juvenile chickens. Newly hatched broiler chickens were fed either a low zinc (10 mg/kg diet) or a zinc-adequate (68 mg/kg diet) soy protein-based purified diet. Cell proliferation in the growth plate was evaluated with bromodeoxyuridine (BrdU) labeling. Apoptosis was assessed using the terminal deoxynucleotidyl transferase-mediated dUTP nick en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 39 publications
2
46
0
2
Order By: Relevance
“…The effect of Zn supplementation on bone development may be due to its direct impact on hormonal growth mediators. The anabolic effect of insulin-like growth factor 1 on osteoblasts is enhanced by Zn (Wang et al, 2002). Moreover, the higher bioavailability of ZnGly indicates that more Zn was absorbed, and not only deposited in bone tissue compared with ZnO, also influenced cell function through its effects on hormones and growth factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of Zn supplementation on bone development may be due to its direct impact on hormonal growth mediators. The anabolic effect of insulin-like growth factor 1 on osteoblasts is enhanced by Zn (Wang et al, 2002). Moreover, the higher bioavailability of ZnGly indicates that more Zn was absorbed, and not only deposited in bone tissue compared with ZnO, also influenced cell function through its effects on hormones and growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the ZnGly50 group presented higher insulinlike growth factor 1 (IGF-1) levels compared with the control group. It is suggested that IGF-1 locally produced in the tissues plays a more important role in growth than that circulating IGF-1 and the produced by the liver (Wang et al, 2002). Cellular changes, which are induced by reduced Zn available from blood supply, are locally observed in areas located away from blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zn is an essential nutrient for life required for many aspects of fetal growth and plays important roles in both prenatal and postnatal bone development. In fact, studies examining effects of Zn deficiency in animal models have shown that mild to severe Zn deficiency disturbs skeletal growth and maturation (Eberle et al, 1999;Wang et al, 2002). Animals fed on Zn-deficient diets have impairment in growth plate chondrocyte proliferation (Rossi et al, 2001;Wang et al, 2002) and bone mass (Eberle et al, 1999).…”
Section: Fig1: Lateral View Of the 20-days-old Fetuses Showing The Crmentioning
confidence: 99%
“…In fact, studies examining effects of Zn deficiency in animal models have shown that mild to severe Zn deficiency disturbs skeletal growth and maturation (Eberle et al, 1999;Wang et al, 2002). Animals fed on Zn-deficient diets have impairment in growth plate chondrocyte proliferation (Rossi et al, 2001;Wang et al, 2002) and bone mass (Eberle et al, 1999). Bone formation in Zn-deficient animals is also characterized by retarded growth plate activity and is associated with reduced cancellous and trabecular volume (Oner et al, 1984;Rossi et al, 2001).…”
Section: Fig1: Lateral View Of the 20-days-old Fetuses Showing The Crmentioning
confidence: 99%